The thermal evolution of planetesimals during accretion and differentiation: consequences for dynamo generation by thermally-driven convection - Dodds, K; Bryson, J; Neufeld, J; Harrison, R (Wiley, 2021)
The meteorite paleomagnetic record indicates that differentiated (and potentially, partially differentiated) planetesimals generated dynamo fields in the first 5-40 Myr after the formation of calcium-aluminium-rich inclusions (CAIs). This early period of dynamo activity has been attributed to thermal convection in the liquid cores of these planetesimals during an early period of magma ocean convection. To better understand the controls on thermal dynamo generation in planetesimals, we have developed a 1D model of the thermal evolution of planetesimals from accretion through to the shutdown of convection in their silicate magma oceans for a variety of accretionary scenarios. The heat source of these bodies is the short-lived radiogenic isotope 26Al. During differentiation, 26Al partitions into the silicate portion of these bodies, causing their magma oceans to heat up and introducing stable thermal stratification to the top of their cores, which inhibits dynamo generation. In ‘instantaneously’ accreting bodies, this effect causes a delay on the order of > 10 Myr to whole core convection and dynamo generation while this stratification is eroded. However, gradual core formation in bodies that accrete over > 0.1 Myr can minimise the development of this stratification, allowing dynamo generation from ∼ 4 Myr after CAI formation. Our model also predicts partially differentiated planetesimals with a core and mantle overlain by a chondritic crust for accretion timescales > 1.2 Myr, although none of these bodies generate a thermal dynamo field. We compare our results from thousands of model runs to the meteorite paleomagnetic record to constrain the physical properties of their parent bodies.